Catalytic conversion of limonene over acid activated Serra de Dentro (SD) bentonite - Fernandes, C. (2021)
A series of acid-activated clay catalysts were prepared from a purified bentonite, rich in structural iron, collected at Serra de Dentro on the island of Porto Santo. The purified bentonite exhibited a surface area of 130 m2 g 1 which increased to values as high as 500 m2 g 1 following activation with 4M HCl at 95 8C for 30 min (SD-4M-95-30). The ability of the activated samples to convert limonene to p-cymene was evaluated using a reaction time of 15 min at 80 8C. The sample prepared using 3M HCl at 95 8C for 30 min (SD-3M-95-30) offered the optimum combination of surface area (470 m2 g 1 ) and acidity (0.26 mmol g 1 ) and 95% of the limonene was converted to product. About 15% of the product mixture was p-cymene whilst non-volatile products and polymeric species made up 54% of the product mixture. The presence of iron in the octahedral sheet of the SD bentonite appears responsible for the dehydrogenation activity. TG–MS analysis of acid activated samples, saturated with cyclohexylamine, reflected the dehydrogenation capabilities of the catalysts in that SD-3M-95-30 produced the most benzene and aniline as decomposition/ transformation products.